2005
DOI: 10.1016/j.ejcts.2005.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair for concomitant multilevel aortic disease☆

Abstract: Simultaneous abdominal and thoracic endovascular repair for multilevel aortic disease is feasible and could be a viable alternative in high-risk patients, who otherwise may not be suitable candidates for conventional repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…One of the largest previously published reports of simultaneous TEVAR and EVAR also demonstrated 0% paraplegia; however, this study only included four patients, most of which were at low risk for SCI (short aortic segment covered, no involvement of the left subclavian artery, elective nature of procedure). 12 Thus, although simultaneous procedures would seemingly be at higher risk for SCI given no time for collateral formation, in our small study, this did not occur.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…One of the largest previously published reports of simultaneous TEVAR and EVAR also demonstrated 0% paraplegia; however, this study only included four patients, most of which were at low risk for SCI (short aortic segment covered, no involvement of the left subclavian artery, elective nature of procedure). 12 Thus, although simultaneous procedures would seemingly be at higher risk for SCI given no time for collateral formation, in our small study, this did not occur.…”
Section: Discussionmentioning
confidence: 78%
“…1,[9][10][11] Fewer case reports have evaluated concomitant endovascular repair of both aortic segments. [12][13][14] We report our experience treating combined thoracic and abdominal aortic aneurysms simultaneously with endoluminal stent grafts. To our knowledge, it is the largest series of combined TEVAR and EVAR for multilevel aortic disease.…”
mentioning
confidence: 99%
“…Castelli et al 3) reported that simultaneous ET for concomitant aneurysms is feasible, which is attractive in terms of minimal invasiveness and safety. On the other hand, it is known that ET for shaggy aorta has a high risk of stroke and bowel ischemia, 1,4) and some articles have reported cases of shaggy aorta that were treated by ET using ECC or other protection devices such as an intra-aortic filter catheter against debris.…”
Section: Discussionmentioning
confidence: 99%
“…Although a staged operation could decrease the procedure-related mortality, the rupture of a residual aneurysm could occur while waiting for the second operation [1]. Since the advent of endovascular repair, several authors have asserted the effectiveness of simultaneous placement of separate stent grafts without a greater risk of serious procedure-related complications than with surgical repair [2,3]. However, there might be two drawbacks to one-stage endovascular repair in multilevel aortic disease.…”
Section: Discussionmentioning
confidence: 99%